Bagai Makan Buah Simalakama: Resistensi Perempuan Terhadap Lembaga Sosial Keluarga dalam Catatan Hati Seorang Istri - Sholihah, Alvia Mustafidatus; Atikurrahman, Moh; Siregar, Wahidah Zein Br. (Universitas Ahmad Dahlan, 2023)
This article aims to describe the figure of feminine resistance by depicting a wife's life in Catatan Hati Seorang Istri (Notes of a Wife's Heart). In Asma Nadia's prose, the narrative highlights domestic problems often experienced by third-world women who usually are faced with a dilemma between matters of domestic space and access to public space. This article refers to Naomi Wolf's view that feminism must fulfill if it is to be called a resistance movement: independence, altruism, persistence, courage, resilience, and willingness to sacrifice. The results of the study show that Wolf's view of power feminism is in the form of women's resistance figures, namely: (1) awareness of the power of women as independent women; (2) the way of thinking and acting of female characters who prioritize the interests of their husbands and children rather than their interests as strength; (3) firm and sure of the chosen decision; (4) dare to voice opinions on their choices; (5) the struggle of a woman when faced with a dilemma in the domestic and public spheres; and (6) sacrifice for the decision of the path of his own choice of life.